HIV, HSV-2 and syphilis among married couples in India: patterns of discordance and concordance. Issue 6 (24th August 2011) - Arora, Paul; Nagelkerke, Nico; Sgaier, Sema K; Kumar, Rajesh; Dhingra, Neeraj; Jha, Prabhat
Abstract : Objectives: Differences in sexual networks probably explain the disparity in the scale of HIV epidemics in sub-Saharan Africa and India. HIV and sexually transmitted infection (STI) discordant couple studies provide insights into important aspects of these sexual networks. The authors quantify the role of male sexual behaviour in HIV transmission in married couples in India. Methods: The authors analysed patterns of HIV and STI discordance in married couples from two community surveys in India: the National Family Health Study-3 for HIV-1 and the Centre for Global Health Research health check-up for HSV-2 and syphilis. A statistical model was used to estimate the fraction of infections introduced by each of the two partners. Results: Only 0.8%, 16.0% and 3.5% of couples were infected (either partner or both) with HIV-1, HSV-2 and syphilis, respectively. A large proportion of infected couples were discordant (73.0%, 56.3% and 84.2% for HIV-1, HSV-2 and syphilis, respectively). This model estimated that, among couples with any STI, the male partner introduced the infection the majority of the time (HIV-1: 85.4%, HSV-2: 64.1%, syphilis: 75.0%). Conclusions: Male sexual activity outside of marriage appears to be a driving force for the Indian HIV/STI epidemic. Male client and female sex worker contacts should remain a primary target of the National AIDS Control Program in India.